2018
DOI: 10.1111/jan.13737
|View full text |Cite
|
Sign up to set email alerts
|

The effect of preparation strategies, qualification and professional background on clinical nurse educator confidence

Abstract: This study identifies several preparation strategies that significantly enhance clinical educator confidence and readiness for their complex role. These preparation strategies drawn from the Vietnamese context, provide important examples for the wider nursing community to consider.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 46 publications
5
16
0
1
Order By: Relevance
“…Previous work in this area has reported on the preparation of nurses to be clinical educators and facilitators for undergraduate or preregistration students (Andrews & Ford, ; Hewitt & Lewallen, ; Lee et al, ; Nguyen et al, ) but there is little understanding of how specialist nurses and facilitators are prepared to facilitate learning during CPD. This study provides insight into the perceptions of specialist nurses and facilitators of an EDP designed to prepare them to teach about end‐of‐life care to generalist front‐line staff.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous work in this area has reported on the preparation of nurses to be clinical educators and facilitators for undergraduate or preregistration students (Andrews & Ford, ; Hewitt & Lewallen, ; Lee et al, ; Nguyen et al, ) but there is little understanding of how specialist nurses and facilitators are prepared to facilitate learning during CPD. This study provides insight into the perceptions of specialist nurses and facilitators of an EDP designed to prepare them to teach about end‐of‐life care to generalist front‐line staff.…”
Section: Discussionmentioning
confidence: 99%
“…In training to deliver end-of-life care, Selman et al (2015) found Previous work in this area has reported on the preparation of nurses to be clinical educators and facilitators for undergraduate or preregistration students (Andrews & Ford, 2013;Hewitt & Lewallen, 2010;Lee et al, 2002;Nguyen et al, 2018)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14,[25][26][27] There was, however, still a substantial proportion of nurse educators who were neither educated as a nurse nor practiced nursing before teaching nursing students. 25,26 As nurse educators substantially shape student experiences through their role modeling behaviors, 28 the use of nonnurses to teach nursing programs can negatively impact students' development of professional identity and professional socialization into nursing. 25,26 On the other hand, there is an improvement in the preparation for nurse educator roles over the years.…”
Section: Impacts Of the Recent Reformsmentioning
confidence: 99%